Implementasi Nilai-nilai Aksiologis dalam Pendidikan Karakter di Sekolah Tahfidz Al Qur’an Al Abidin - Mujiburrohman, Mujiburrohman; Muharromah, Fityatul (TSAQOFAH, 2025)
This research aims to determine the implementation of axiological values ​​in character education. Character education is an effort to shape a person's character, temperament, manners and personality by instilling in him noble values ​​so that these values ​​take root, are embedded in the heart, thoughts, words and deeds and show their influence on life. Having a complete understanding of axiogical values ​​will strengthen the cultivation of character education. The research uses qualitative methods with data collection techniques through interviews, observation and document review. The results show that the implementation of axiological values ​​focuses more on moral conduct with an approach to instilling character education in both learning and daily activities. The challenges faced in the implementation process are family synergy that has not been maximized, personal factors, friendship environment and the development of social media.